Diagnosis and staging of hepatobiliary malignancies: Potential incremental value of (18)F-FDG-PET/MRI compared to MRI of the liver - Obmann, Verena Carola; Grosse-Hokamp, Nils; Alberts, Ian; Fulton, Nicholas; Rassouli, Negin; Siegel, Christopher; Avril, Norbert; Herrmann, Karin Anna (Nuklearmedizin - NuclearMedicine, 2021)
Objective The purpose of the study was to investigate the potential added value of 18F-FDG-PET/MRI (functional information derived from PET) over standard diagnostic liver MRI (excellent soft tissue characterization) in diagnosing and staging suspected primary hepatobiliary malignancies including extrahepatic cholangiocarcinoma (ECC), intrahepatic cholangiocellular carcinoma (ICC) and gallbladder cancer (GBCA).Methods Twenty consecutive patients with suspected hepatobiliary malignancy were included in this retrospective study. All patients underwent combined whole-body (WB) 18F-FDG-PET/MRI including contrast-enhanced MRI of the liver, contrast-enhanced WB-MRI and WB 18F-FDG-PET. Two experienced readers staged hepatobiliary disease using TNM criteria: first based on MRI alone and then based on combined 18F-FDG-PET/MRI. Subsequently, the impact of FDG-PET/MRI on clinical management compared to MRI alone was recorded. Histopathologic proof served as the reference standard.Results Hepatobiliary neoplasms were present in 16/20 patients (ECC n = 3, ICC n = 8, GBCA n = 5), two patients revealed benign disease, two were excluded. TNM staging with 18F-FDG-PET/MRI was identical to MRI alone in 11/18 (61.1 %) patients and correctly changed the stage in 4/18 (22.2 %), resulting in a change in management for 2/4 patients (11.1 %). 18F-FDG-PET/MRI was false-positive in 3/18 cases (16.7 %). Both MRI and 18F-FDG-PET/MRI were falsely positive in 1 case without malignancy.Conclusions A small incremental benefit of 18F-FDG-PET/MRI over standard MRI of the liver was observed. However, in some cases 18F-FDG-PET/MRI may lead to false-positive findings. Overall there is seemingly limited role of 18F-FDG-PET/MRI in patients with suspected hepatobiliary malignancy.
Keywords: PET/MRI; MRI; whole-body staging; cholangiocellular carcinoma; gallbladder carcinoma; diffusion-weighted imaging